ARCHITECTURAL DECORATION OF THE CHURCH IN DRANDA (ALTAR BARRIER AND WESTERN FACADE): AN ATTEMPT OF VIRTUAL RECONSTRUCTION - Endol'ceva, Ekaterina Ur'evna; Bystrickij, Nikolaj Igorevic; Dryga, Daniil Olegovic; Karnausenko, Ella Nikolaevna; Karnausenko, Aleksandr Dmitrievic; Kazennova, Lubov' Konstantinovna (History, Archeology and Ethnography of the Caucasus, 2025)
The purpose of this research is to create a reliable virtual reconstruction of the altar barrier and, possibly, the external cladding (mainly the western facade) of the church in Dranda (Gulripsh rayon, Republic of Abkhazia). All known fragments of the architectural decoration of this church were examined in detail. The available fragments are currently distributed over three locations: the funds of the Abkhaz State Museum in Sukhum, the narthex of this church, the funds of the Ecclesiastical Archaeological Museum of the Holy Metropolis of Abkhazia. In addition, there are published phototypes of two now lost slabs with complex multi-figure compositions that came from the same church. The composition of the scientific work on the reconstruction of the studied monument consisted of the following stages: research and digitization of the interior of the Church of the Assumption in the village of Dranda and fragments of architectural decoration stored in its narthex. 3D models were created, fragments (stones) stored in the funds of the Church and Archaeological Museum of the Holy Metropolis of Abkhazia were analyzed and attributed. At the last stage, a 3D model of the altar barrier and, partly, the western facade was created and verified. As a result of the research and digitization of existing fragments, a hypothesis has been put forward about the original appearance of the altar barrier and the decoration of the western facade of the church in Dranda. The slab, which may have adorned the western facade, apparently reproduces a fragment of an abbreviated scene of the Last Judgment (Christ on the throne and four angels). Thanks to the found stylistic and iconographic analogies, the restored architectural decoration (small forms and external decoration) is organically integrated into the artistic context of Eastern Christian art of the 10th–11th centuries. (Byzantium, certain regions of Georgia).
Keywords: reliefs; plastic; Last Judgment; architectural decoration; altar barrier; sculpture; Dranda